Disclosure by Politicians - Djankov, Simeon; La Porta, Rafael; Lopez-de-Silanes, Florencio; Shleifer, Andrei (2012)
We collect data on the rules and practices of financial and conflict disclosure by members of Parliament in 175 countries. Although two-thirds of the countries have some disclosure laws, less than one-third make disclosures available to the public, and less than one-sixth of potentially useful information is publicly available in practice, on average. Countries that are richer, more democratic, and have free press have more disclosure. Public disclosure, but not internal disclosure to parliament, is positively related to government quality, including lower corruption.